Hybrid neural network approaches to predict drug–target binding affinity for drug repurposing: screening for potential leads for Alzheimer’s disease - Wu, Xialin; Li, Zhuojian; Chen, Guanxing; Yin, Yiyang; Chen, Calvin Yu-Chian (Frontiers in Molecular Biosciences, 2023)
Alzheimer's disease (AD) is a neurodegenerative disease that primarily affects elderly individuals.Recent studies have found that sigma-1 receptor (S1R) agonists can maintain endoplasmic reticulum stress homeostasis, reduce neuronal apoptosis, and enhance mitochondrial function and autophagy, making S1R a target for AD therapy. Traditional experimental methods are costly and inefficient, and rapid and accurate prediction methods need to be developed, while drug repurposing provides new ways and options for AD treatment. In this paper, we propose HNNDTA, a hybrid neural network for drug-target affinity (DTA) prediction, to facilitate drug repurposing for AD treatment. The study combines protein-protein interaction network analysis, the HNNDTA model, and molecular docking to identify potential leads for AD. The HNNDTA was constructed using 13 drug encoding networks and 9 target encoding networks with 2506 FDA-approved drugs as the candidate drug library for S1R and related proteins. Seven potential drugs were identified using network pharmacology and DTA prediction results of the HNNDTA model. Molecular docking simulations were further performed using the AutoDock Vina tool to screen Haloperidol and Bromoperidol as lead compounds for AD treatment. ADMET evaluation results indicated that both compounds had good pharmacokinetic properties and were virtually non-toxic. The study proposes a new approach to computer-aided drug design that is faster, more economical, and can improve hit rates for new drug compounds. The results of this study provide new lead 1 Wu et al. compounds for AD treatment, which may be effective due to their multi-target action. HNNDTA is freely available at https://github.com/lizhj39/HNNDTA.